Using Solar Energy and Photovoltaic Power in Air-Conditioning Processes by Adsorption Technique - Jabbar Kh. Mohammed (Journal of Madenat Alelem University College, 2019)
The research is present the heat-driven adsorption chiller performance by using low temperature water which be extracted from the solar energy through using photovoltaic solar panels and solar thermal collectors as a main energy source. The adsorption system employs the silica gel-water as the adsorbent. Also this system has an advantage such as the maintenance is low, no major parts movement and environmental friendly. The numerical simulations have been carried out for heat sources temperatures ranged between 60-80°C, chilled water and cooling from 15 °C to 35 °C respectively. Program in FORTRAN was built to achieve the numerical simulation for adsorption system. The results indicated the coefficient of performance for lower hot water temperature is increased with time processes of heating or cooling. The refrigeration capacity for high hot water temperature is increased with time processes of heating or cooling while the effect of low hot water temperature is low